Cerebral Blood Flow and Other Predictors of Responsiveness to Erenumab and Fremanezumab in Migraine—A Real-Life Study - Nowaczewska, Magdalena; Straburzyński, Marcin; Waliszewska-Prosół, Marta; Meder, Grzegorz; Janiak-Kiszka, Joanna; Kaźmierczak, Wojciech (Frontiers in Neurology, 2022)
Introduction: Monoclonal antibodies (mAbs) showed efficacy in migraine prevention. The aim of this study was to check if baseline clinical parameters and cerebral blood flow (CBF) measured by transcranial Doppler (TCD) may help predicting mAbs efficacy. Methods: Electronic charts of migraineurs treated with erenumab or fremanezumab, with baseline TCD evaluations were collected, including data on migraine type, pain localization, monthly migraine days (MMD), medication overuse headache (MOH), mean blood flow velocity (Vm) and pulsatility index (PI) in cerebral arteries. Results: 123 patients were enrolled, mean age 38,75 years, 87 with chronic migraine, 61 with MOH, 72 were good responders (GR) and reported ≥50% reduction in MMD, 43 ≥75% reduction in MMD. Baseline Vm values in MCAs were significantly lower in GR as compared with non-responders. MAbs responsiveness ≥50% was positively associated with unilateral pain localization (OR: 6.53,95% CI:2.01-23.93;p=0,003) and HIT-6 score (OR: 1.14, 95% CI:1.01-1.30;p=0,036) whereas negatively associated with Vm in right MCA (OR: 0.96, 95% CI:0.92-0.99;p=0,012), and having no relatives with migraine (OR: 0.40, 95% CI:0.16-0.95;p=0,040). Conclusions: Baseline Vm in MCA is lower in mAbs GR as compared with non-responders which may reflect increased secretion of CGRP with further vasodilation in GR. Simple clinical features and baseline CBF in anterior circulation might help to predict patient's responsiveness.